Gwarancje jakości prawa w przepisach Ustawy z dnia 6 marca 2018 r. – Prawo przedsiębiorców - Etel, Maciej (Studia Prawa Publicznego, 2023)
The legal situation of entrepreneurs in Poland is determined by a huge number of normative acts. However, the legislator’s interest in entrepreneurs and economic activity should not come as a surprise. Indeed, an economically conscious state cannot afford to be indifferent to the entrepreneur and, even in a market economy, should normatively regulate the rules for undertaking, performing and terminating economic activities and shape the rights and obligations in this regard. It must also be remembered that the matter to be regulated is very broad, complex and multi- faceted, and the law must take into account the enormous diversity of relationships, roles, events and facts in which the entrepreneur functions in connection with their economic activity. On this basis, it can be assumed that the law that determines the rules for undertaking, performing and terminating economic activities is natural and necessary. Nevertheless, it should be clearly emphasized that the quality of the law shaping the situation of entrepreneurs and their economic activities should be prioritized as an overriding and fundamental value – the appropriate quality of the law (i.e., properly enacted and applied) is a sine qua non of economic development, while a lack of quality in the sphere of lawmaking and application makes it difficult or even impossible for entrepreneurs to function, and thus leads to stagnation or regression in the economy. The study is focused on the guarantees of the quality of lawmaking and application empowered by the Act of 6 III 2018 – Entrepreneurs’ Law. Analyzing the provisions of this act makes it possible to identify the regulations focused on the quality of lawmaking and application. The study also aims to answer the question: Can the guarantees set out in this Act contribute to improving the quality of lawmaking and application of the law on the undertaking, conduct and termination of economic activity?